2022
DOI: 10.3390/ani12050585
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira in Slaughtered Fattening Pigs in Southern Italy: Serological Survey and Molecular Typing

Abstract: Leptospirosis is a re-emerging zoonosis of worldwide significance; a wide spectrum of wild and domestic animal species act as natural or accidental hosts. Swine can act as maintenance or accidental hosts of pathogenic Leptospira spp. This study aimed at investigation of Leptospira spp. prevalence and diversity in slaughtered pigs in southern Italy (Sicily). In total, 55 samples of kidneys and blood were collected. Microscopic agglutination test and real-time PCR were performed to detect pathogenic and intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Unexpectedly, positivity for serogroups reported to be the most frequently involved in feline leptospirosis in Europe, according to the European consensus statement on leptospirosis, such as Canicola, Grippotyphosa, Sejroe and Icterohaemorrhagiae [ 1 , 2 ], was not detected. Antibodies against the serovars Poi, Arborea, and Mini were never reported before in cats; however, the most frequent seroreactivity found in the present study involved serovars previously described in other hosts in Italy, such as wild boars [ 59 ], pigs [ 60 , 61 ], wolves [ 62 ], Hystrix cristata [ 56 ], horses [ 52 , 55 ], dairy cattle [ 54 ] and wild ruminants [ 51 ], kennel dogs [ 42 , 43 , 46 ] and humans [ 50 ]. Moreover, Tagliabue et al [ 43 ] reported in various host species, antibody-positivity against serogroups Australis (dogs, wild boars, horses, hares, swine, foxes and rodents), Sejroe (cattle, sheep, goats and buffaloes), Icterohaemorrhagiae (dogs, goats and foxes), Pomona (swine, cattle and wild species) and Grippotyphosa (hares).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Unexpectedly, positivity for serogroups reported to be the most frequently involved in feline leptospirosis in Europe, according to the European consensus statement on leptospirosis, such as Canicola, Grippotyphosa, Sejroe and Icterohaemorrhagiae [ 1 , 2 ], was not detected. Antibodies against the serovars Poi, Arborea, and Mini were never reported before in cats; however, the most frequent seroreactivity found in the present study involved serovars previously described in other hosts in Italy, such as wild boars [ 59 ], pigs [ 60 , 61 ], wolves [ 62 ], Hystrix cristata [ 56 ], horses [ 52 , 55 ], dairy cattle [ 54 ] and wild ruminants [ 51 ], kennel dogs [ 42 , 43 , 46 ] and humans [ 50 ]. Moreover, Tagliabue et al [ 43 ] reported in various host species, antibody-positivity against serogroups Australis (dogs, wild boars, horses, hares, swine, foxes and rodents), Sejroe (cattle, sheep, goats and buffaloes), Icterohaemorrhagiae (dogs, goats and foxes), Pomona (swine, cattle and wild species) and Grippotyphosa (hares).…”
Section: Discussionsupporting
confidence: 43%
“…Although in Italy, cases of leptospirosis are widely reported in dogs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and humans [ 47 , 48 , 49 , 50 ] and Leptospira spp. infection has been reported in other host species [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], only one study so far has investigated Leptospira spp. prevalence in cats [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results also confirm the usefulness of using multiple diagnostic approaches to confirm leptospirosis. Indeed, the used Real-time PCR method can detect all pathogenic Leptospira species currently known [ 54 , 55 ] with efficiency, sensitivity, and specificity, allowing to overcome some limits of serological investigation (e.g., failure of an early diagnosis, low sensitivity). On the other hand, routine PCR does not allow for identifying the species/serovar involved, so serology has still a relevant role in epidemiological studies also allowing for cost containment.…”
Section: Discussionmentioning
confidence: 99%
“…The MLST was carried out by the Italian National Reference Centre for Leptospirosis, at the Istituto Zooprofilattico Sperimentale della Lombardia e dell’Emilia Romagna, Brescia (Italy) [ 43 , 44 , 45 , 46 ]. Seven housekeeping genes were sequenced: glm U, pnt A, suc A, tpi A, pfk B, mre A, and cai B, based on scheme 1 proposed by Boonsilp in 2013 [ 44 , 47 ]. Nucleotide sequences were assembled using the SeqMan module of the Lasergene sequencing analysis software package (DNASTAR Inc., Madison, WI, USA) or using Bionumerics software ver.…”
Section: Methodsmentioning
confidence: 99%